Motyw Aurory w antycznej poezji chrześcijańskiej - Adamiak, Jarosław (Vox Patrum, 2013)
The theme of Dawn, which is present in the epics of Homer and later on in the poetry of Vergil and Ovid, was also present in ancient Christian poetry. This, on one side was due to ancient education, that included works by classical authors. On the other side, it resulted from the desire by Christian artists to mimic pagan masters. The theme of dawn is an example of acquasition of poetic patterns, but it also shows the original thought of Christian poets who gave it new meaning, identifying the Aurora with Christ.